THE POTENTIAL AND WORKING VOCAL RANGE OF GIRLS AGED 6 TO 12 - Ivane, Madara; Trinīte, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Aim of this study is to determine the potential and working vocal range in the results of objective and subjective voice range evaluation in elementary school girls – solo singers. Theoretical part contains review of other authors’ studies related to child’s voice range from 6 to 12 years. Practical part of the study offered making of the phonetogram by using Voice Range Profile software (CSL 4500, Kay Pentax, USA) as an objective method for voice range evaluation. For subjective voice analysis, a voice range evaluation in form of vocal exercises was performed. It is understood that the objective voice evaluation reflects the potential of girls’ voice range, while the subjective evaluation – current working voice range. Fourteen girls attending solo singing classes were part of this study (medium age: 9.14 years; SD: 1.79 years; age range: 6-12 years). Three study groups were formed: 6-8 year old girls (n = 5); 9-10 year old girls (n=5); 11-12 year old girls (n=4). In 6-8 year old girls, VRP was from sol# (204.31 Hz, SD: 26, 05) to do3 (1047.72, SD: 409.70), but in subjective voice range evaluation, it was from la (220.28 Hz, SD: 18.88) to fa2 (775.90 Hz, SD: 70.64). In the group from 9-10 year old girls VRP range was from fa (171.25 Hz, SD: 16.03) to re#3 (1224.47 Hz, SD: 156.12), but current working voice range was from sol (208.79 Hz, SD: 24.90) to sol#2 (842.20 Hz, SD: 132.80). In 11-12 years old girls objective VRP results were fa# (186.54 Hz, SD: 27.76) to re#3 (1277.61 Hz, SD: 80.09), while from sol (208.23 Hz, SD: 12.16) to si2 (933.46 Hz, SD: 175.22) the work range was. In discussion part findings by other authors are compared to the objective and subjective voice range data acquired in this study. It is concluded that potential child’s voice range in girls 6-12 years of age exceeds two octaves yet working range reaches up to two octaves.